Egypt and armed conflicts in the Horn of Africa (Journal of Oriental Studies, 2016)
The armed conflicts in the Horn of Africa and the regional policy of the Arab Republic of Egypt to resolve these conflicts are considered in the article. The author appreciates the Egyptian peace initiatives in the region and comes to the conclusion that the Horn of Africa region is an important direction of the regional foreign policy of Egypt.
Keywords: Egypt; the Horn of Africa region; armed conflicts; the problem of security.